PENGARUH ONLINE LEARNING BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR KOGNITIF PADA MATA KULIAH TEORI SOSIOLOGI MODERN - Kuntari, Septi; Setiawan, Rizki; Lindawati, Yustika Irfani (Universitas Muria Kudus, 2021)
The purpose of this study is to analyze the effect of online learning based on problem based learning (PBL) on cognitive learning outcomes in modern sociology theory courses.The research method used is an experiment that involves a one group pretest posttest design. The research population is students of sociology education at Sultan Ageng Tirtayasa University. The sample was determined purposively and obtained by 3rd semester students in the modern sociology theory course. The independent variable is PBL-based online learning, while the dependent variable is cognitive learning outcomes. The instrument was tested for construct validity through expert judgment and empirical validation was carried out by testing the instrument on students who had already received material on modern sociological theory. Before being used in experimental research, the data was tested for validity and reliability.The results showed that there was an effect of PBL-based online learning on cognitive learning outcomes, namely through hypothesis testing using a t-test at a significance level of 5%, obtained a t-value of 12.895 in class A and a t-value of 8.547 in class B, with the acquisition of each significance of 0.00 is smaller than 0.05. So, class A used PBL with t count t table (12,8952,048) and class B used PBL with t count t table (8,5472,048). So H0 is rejected, so it can be concluded that PBL-based online learning is able to improve cognitive learning outcomes.